Design, delivery and evaluation of a simulation‐based workshop for health professional students on falls prevention in acute care settings - Debra Kiegaldie; Debra Nestel; Elizabeth Pryor; Cylie Williams; Kelly‐Ann Bowles; Stephen Maloney; Terry Haines (Wiley, 2019)
Abstract Aims and objectives To describe the design, delivery and evaluation outcomes of a simulation‐based educational workshop to teach a patient‐centred falls prevention strategy to health professional students tasked with implementing the strategy during clinical placement. Background Falls are among the most common and costly threat to patient safety. The Safe Recovery Programme (SRP) is an evidence‐based, one‐to‐one communication approach with demonstrated efficacy at preventing falls in the postgraduate context. Simulation‐based education (SBE) is commonly used to address issues of patient safety but has not been widely incorporated into falls prevention. Methods This study was a Pre-Post‐test intervention design. Health professional students were taught how to deliver the SRP in an SBE workshop. The workshop incorporated content delivery, role‐play simulations and interactions with a simulated patient. Students completed surveys immediately before and after the workshop and after clinical placement. Linear and logistic regression analysis was undertaken to identify differences within each pairwise comparison at the three time points. Qualitative free text responses underwent content analysis. Results There were 178 students trained. The educational design of the programme described in this paper was highly valued by students. Following the workshop, students' falls knowledge increased and they correctly identified evidence‐based strategies except bedrail use and patient sitters. Following clinical placement, fewer SBE students correctly identified evidence surrounding bed alarm use. Students became more confident about falls communication post‐SBE; however, this confidence decreased postclinical placement. Motivation to implement the SRP decreased between postworkshop and postclinical placement time points. Conclusions Falls research often includes educational components but previous studies have failed to adequately describe educational methods. Students learnt about best evidence falls prevention strategies using interactive educational methodologies with a workshop viewed by students as being well‐designed and assisting their learning from theory to practice. While students valued the delivery of the SRP using SBE, confidence and motivation to implement falls strategies were not sustained following clinical placement. A programme of education including SBE can be used to support the delivery of falls‐based education, but further research is needed to identify what factors may influence student's motivation and confidence to implement falls prevention strategies during clinical placement.